Explicating the Educational Implications of Caring Thinking from the Perspective of Matthew Lipman - Izadi Shaldehi , Majid; Salimi, Ladan; Rasouli , Seyyedeh Esmat (Assessment and Practice in Educational Sciences, 2026)
This study aimed to identify and interpret the educational implications of the philosophical foundations of Matthew Lipman’s caring thinking framework using Frankena’s deductive method. This qualitative study employed a systematic literature review and semi-structured expert interviews to extract the philosophical components, indicators, and conceptual structures associated with caring thinking. Data sources included peer-reviewed publications, educational research documents, and works authored by Lipman and leading scholars in the Philosophy for Children (P4C) tradition. Interviews were conducted with specialists in philosophy of education, P4C practitioners, and curriculum experts selected through purposive sampling. Data analysis followed an iterative coding process in which extracted concepts were categorized into components and indicators and subsequently interpreted through Frankena’s ethical deduction framework, which includes conceptual analysis, examination of principles and assumptions, argument evaluation, and inferential conclusion building. Inferential analysis revealed that caring thinking comprises five main components—acceptance and attention to diversity, interpersonal communication development, respect for self and others, enhancement of self-awareness, and cultivation of communication and problem-solving skills. Deductive interpretation indicated that each component possesses distinct philosophical underpinnings and educational implications, including the promotion of reflective reasoning, ethical sensitivity, collaborative dialogue, and social responsibility. The model further demonstrated that caring thinking functions as an integrative construct linking cognitive, emotional, and interpersonal dimensions within educational practice. Overall, the inferential framework confirmed that caring thinking embodies both normative and pedagogical significance, making it essential for contemporary curriculum design and learner development. The study concludes that caring thinking, as conceptualized by Lipman, represents a multidimensional philosophical foundation with substantial educational relevance and should be systematically integrated into instructional design, teacher preparation, and curriculum policy to promote holistic learner development.